On special submanifolds of an ? - Kenmotsu Manifold - Doğan, Saadet; Karadağ, Müge (My University, 2014)
In this paper, we study some special type of submanifolds such as Z-umbilical submanifolds associated with an M-vector field Z on a submanifold M of an ?- Kenmotsu manifold M and we find some interesting results.

Bu çalışmada bir ?- Kenmotsu manifoldunun bir alt manifoldu üzerinde bir M - vektör alanı Z ile birleştirilmiş Z-umbilik alt manifold kavramlarını inceledik ve bir takım ilginç sonuçlara ulaştık.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Z-umbilical submanifolds; ?- Kenmotsu manifolds; Z-umbilik altmanifold; ?- Kenmotsu manifold